Preparation and properties of ferroelectric BaTiO3 thin films produced by the polymeric precursor method - Lee, E. J. H.; Pontes, F. M.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Araujo, E. B.; Eiras, J. A. (Springer Nature, 2000)
Ferroelectric barium titanate thin films were produced by the polymeric precursor method. In this technique, the desired metal cations are chelated in a solution using a hydroxycarboxylic acid as the chelating agent. Barium carbonate and titanium IV isopropoxide were used as precursors for the citrate solution. Ethylene glycol and citric acid were used as polymerization/complexation agents for the process. The crystalline structure of the film annealed at 700 °C had a single perovskite phase with a tetragonal structure. The BaTiO3 film showed good P-E hysteresis loops and C-V characteristics due to the switched ferroelectric domains.
Keywords: Atomic force microscopy; Barium titanate; Complexation; Ferroelectricity; Glycols; Hysteresis; Perovskite; Polymerization; Scanning electron microscopy; Thin films; X ray diffraction; Metal-ferroelectric-metal capacitors; Polymeric precursor method; Ferroelectric materials